Responsibility, Structural Injustice, and Structural Transformation. Issue 1 (1st January 2018) - Lu, Catherine
ABSTRACT: This author's reply responds to five main issues raised by the commentators. The first two issues regard the concept of structural injustice and agents' responsibility for it. What kind of responsibility is generated by structural injustice? How is it distinct from responsibility related to the liability of agents for interactional injustice? Addressing these issues requires clarifying how my understanding of structural injustice draws on and differs from Iris Marion Young's account. A third issue addressed in this reply regards the question of what institutional and structural reforms or initiatives would promote emancipatory versus regressive responses to structural injustice. This question is particularly sharp in the case of redressing the injustice and alienation of settler colonial social structures on Indigenous peoples. A fourth issue relates to the question of what useful role states and international law, especially human rights law, may play in making progress towards eliminating various forms of structural injustice, such as those related to gender oppression. This response will finally address a fifth issue about reconciliation as a regulative ideal, and whether my conception of reconciliation as non-alienation of various kinds invites a tragic reading of the pursuit of reconciliation in politics.